Perceived barriers to accessing physical therapy services in Florida among individuals with low back pain - Hanney, W.J.; Munyon, M.D.; Mangum, L.C.; Rovito, M.J.; Kolber, M.J.; Wilson, A.T. (Frontiers in Health Services, 2022)
Background: Low back pain (LBP) affects up to 84% of adults and physical therapy (PT) has been reported to be an effective approach to conservative care. For those individuals with LBP referred to PT, the decision to initiate and follow through with care is influenced by numerous factors. Currently, a paucity of evidence exists to identify barriers for patients with LBP to access PT care. Thus, the purpose of this study was to investigate perceived barriers influencing the decision to pursue PT care in the state of Florida. Methods: A purposive survey was administered via Qualtrics ESOMAR. Screener questions ensured candidates had LBP, resided in Florida, and were referred to PT. Participants that met the screener questions were offered an opportunity to participate in the full survey. Once a participant completed the full survey, variables assessing LBP, access to PT services, and potential barriers were analyzed. A partial least squares structural equation model (PLS-SEM) via WarpPLS 7.0 was used to explore which of the perceived barriers had the greatest influence on whether an individual with LBP was able to pursue PT care. Results: The conceptual framework that demonstrated the best fit of direct effects of potential barriers to accessing care included six independent exogenous latent variables: (a) unaware of a PT clinic near their home or work, (b) had children but no childcare for them, (c) had long PT sessions (e.g., 60 minutes), (d) had more than one PT session per week, (e) had fewer days active per week, and (f) exercised fewer times per day. Together the six variables explained 19% of the variance related to following through with care (R2 = 0.19). Conclusions: The ability of an individual with LBP to access PT care in the state of Florida is multifactorial. There appears to be three broad factors that are the primary barriers, which include (a) the logistic ability (location and access to childcare) to attend PT treatment, (b) how much time is dedicated to the PT treatment, and (c) activity frequency of the individual seeking care. These findings support previous conceptual frameworks for predicting PT treatment.